PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, EARNING PER SHARE, DAN PROFITABILITAS PERUSAHAAN TERHADAP STOCK RETURN - -, Justine; Dara, Siti Ruhana (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the influence of Kepemilikan Institusional, Kepemilikan Manajerial arning Per Share (EPS), and profitability on Stock Return in Consumer Non-Cyclicals companies, particularly in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research employs a quantitative method with purposive sampling in selecting the sample. The data is obtained from publicly available financial reports and analyzed using panel data linear regression to examine the impact of each independent variable on the dependent variable. The findings indicate that managerial ownership has a significant partial effect on Stock Return, while institutional ownership, EPS, and profitability do not have a significant impact. These results provide valuable insights for investors in making investment decisions and for corporate management in enhancing financial performance and competitiveness in the capital market. The implications of this study also serve as a reference for stakeholders in formulating more strategic policies to foster corporate growth in the food and beverage industry.